Effects of multimedia annotation on reading comprehension and incidental vocabulary acquisition of Malaysian tertiary ESL students - Tan, Nancy Chiew Ha (2014)
This study investigated the effects of different types of multimedia annotations on reading comprehension and incidental vocabulary acquisition among learners of English as a second language whose English language proficiency is of intermediate level. The subjects were one hundred and twenty eight second and third semester college students enrolled in a teacher-training institute. The subjects were directed to read an electronic reading text in English containing thirty annotated words. Each participant read the text under one of the following conditions: No annotation (Control group), Audio annotation (A group), Audio-Text annotation (AT group), Audio-Picture annotation (AP group) and Audio-Picture-Text annotation (APT group). The instrument used for data collection was a set of reading comprehension test and a set of vocabulary test. The reading comprehension test comprised thirty multiple-choice questions and ten open-ended subjective comprehension questions. The vocabulary test measured the research participants’ ability to recall the meanings of all the target words and to use them in writing (vocabulary production). Two posttests were conducted to compare the research participants’ achievement. The first posttest was carried out immediately after the participants had finished reading the comprehension text assigned to them. The second posttest was administered three weeks later to measure reading comprehension and word retention. The results showed that there was no statistical difference in the reading comprehension, vocabulary recall, and vocabulary production scores between the control group and the multimedia annotation groups across all test points (pretest, immediate posttest, delayed posttest). As for the multimedia-annotation groups, it was found that all multimedia annotations, except audio only format, did increase reading comprehension, vocabulary recall, and vocabulary production scores of the participants. The findings also indicated that among the multimedia annotation configurations, the more annotation format and annotation mode utilized corresponded to higher reading comprehension, vocabulary recall, and vocabulary production scores in immediate and delayed posttests. It was therefore established that all multimedia annotations presented except for audio only format, did indeed have a significant effect in improving reading comprehension and incidental vocabulary acquisition of the research participants.